There and Back Again? Exploring the Real-Time Cognitive Journey of Narrative Transportation. (April 2023) - Tchernev, John M.; Collier, James; Wang, Zheng
Prior research has produced seemingly conflicting indications of whether or not audience members who are transported into a narrative leave themselves and the real world behind. This study proposes that a dynamic perspective can help resolve that conflict. Both traditional static post-exposure and real-time dynamic measures were used to examine four cognitive processes: attention, presence, self-referencing, and real world-referencing. Participants ( N  = 118) were randomly assigned to view one of two television dramas. They provided continuous rating responses during viewing, as well as post-exposure measures of the overall viewing experience. Post-exposure measures indicated that self and real world-referencing were strongly positively correlated with transportation. The dynamic approach to understanding narrative processing, while exploratory in nature, likewise indicated links between the self, the real world, and the narrative world. Presence in the narrative predicted real world-referencing, and self-referencing predicted attention to the narrative, suggesting that when audience members link story content to their own lives, transportation may be enhanced rather than diminished. Strengths, limitations and future directions are discussed.